Future climate change accelerates the invasive rhythm of alien marine species: New insights into the invasive potential of the world's aquaculture species red drum Sciaenops ocellatus - Yongshuang Xiao; Jing Liu; Jiehong Wei; Zhizhong Xiao; Jun Li; Alfonso Aguilar-Perera; Angel Herrera-Ulloa (Ecological Indicators, 2023)
In recent decades, an unprecedented frequency of red drum (Sciaenops ocellatus) escapes from sea cages (i.e., million tail level) has generated enormous pressure on local marine biodiversity and ecosystems. This study aimed to assess the distribution and shifts of hotspot fitness zones for S. ocellatus under global climate change and to identify the trophic levels in the coastal waters of China. The species distribution model (SDM) identified four hotspot fitness zones at a global scale located in the Atlantic Ocean along the Gulf of Mexico and Uruguayan coasts, and in the Pacific Ocean along the Chinese and Australian coasts. Under global warming and climate change, the most suitable habitat for S. ocellatus would expand (448,178.6 km2) and the centre of mass would shift northwards. Stable isotope δ15N and δ13C ratios indicated S. ocellatus has very high ecological competition, within a wide feeding range and high ecological position (δ15N: 10.84 ∼ 12.84 ‰, 11.61 ± 0.62 ‰; δ13C: −15.28 ∼ -17.25 ‰, −16.45 ± 0. 52 ‰) in the escape zone. The results suggested that a wide range of habitats, high reproductive capacity, and ecological niche competition conferred escaped S. ocellatus with a great ability to invade across regions on a global scale.